2012
DOI: 10.1111/j.1465-7287.2012.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impacts of Labor Market and Deterrence Variables on Crime Rates in Mexico

Abstract: Many studies examine the relationship between crime rates and various economic and/or sociodemographic variables in high income countries, but similar efforts for middle and low income countries are less common. Utilizing an 8‐year panel data sample for all 32 states in Mexico, this study assesses the impact of Mexican labor market and deterrence variables on various Mexican crime rates. The principal results indicate that: (1) State gross domestic product (GDP) per capita has ambiguous effect on crime rates u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…The results highlighted the importance of GIP triangle to reduce IHR in a panel of selected countries. Liu et al (2013) investigated the relationship between national scale indicators of socio-economic and demographic factors and crime rates in 32 Mexican states and found that EG, wages and unemployment negatively affect crime rates, while increase federal police force that is helpful to reduce crime rates; however, on the other way around, higher public security expenditures are linked with the higher crime rates in Mexican states. Chu and Tusalem (2013) investigated the role of state to reduce IHR in a panel of 183 nations and found that political instability increases IHR, while anocracies is the strong predictor to influence IHR in a panel of countries.…”
mentioning
confidence: 99%
“…The results highlighted the importance of GIP triangle to reduce IHR in a panel of selected countries. Liu et al (2013) investigated the relationship between national scale indicators of socio-economic and demographic factors and crime rates in 32 Mexican states and found that EG, wages and unemployment negatively affect crime rates, while increase federal police force that is helpful to reduce crime rates; however, on the other way around, higher public security expenditures are linked with the higher crime rates in Mexican states. Chu and Tusalem (2013) investigated the role of state to reduce IHR in a panel of 183 nations and found that political instability increases IHR, while anocracies is the strong predictor to influence IHR in a panel of countries.…”
mentioning
confidence: 99%
“…Their results show that an increase in the crime rate in a specific state negatively affects the per capita GDP growth rate in neighboring states. Liu et al.... (2013) find that wages and unemployment rates are negatively impacted by crime rates in Mexico. According to Albuquerque (2007), in Mexico, homicides are highly concentrated in just some geographic areas of the country, particularly along the US-Mexico border.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Despite the predominant and popular perception that international trade and maquiladora employment are one of the main factors behind border femicide, economic research on violent crime generally shows the opposite: that greater levels of international trade and formal sector employment typically lead to improved socioeconomic outcomes, and that crime and socioeconomic development are usually negatively related. Liu et al (2013) and Liu & Fullerton, Jr. (2015) are examples of scholarship that find this negative relationship in the case of Mexico. This article's contribution to the existing literature is therefore to confirm the latter results in the context of border femicide with the help of a unique high-quality database.…”
Section: Gender Violence and Femicidementioning
confidence: 99%